The application of commercial coconut oil in front of pathologies and human syndromes with emphasis on pathogenic bacteria in the light of scientific evidence (Research, Society and Development, 2020)
Considered one of the main constituents of food bases of the ancient population, since they are taken from Cocos (Cocos nucifera), coconut oil (Coconut Oil) has been used for centuries as a food and water base by the inhabitants of tropical regions. Nowadays, its applicability for improving human health has been proven and replicated, with regard to characters of nutrition, pharmacology, metabolizing, catalysis and thermogenic action. On the other hand, some national business and medical entities point out its application as harmful and pathogenic. Thus, new scientific evidence is brought to light in the analysis and confirmation, since the application in the microbiological antrum remains a factor of uncertainty in its potential. The present study is a laboratory research, of quantitative nature, based on bibliographic and experimental laboratory analyzes, being applied a methodological design of theoretical-empirical inductivity construction and practical laboratory execution, with the objective of testing the application of laboratory tests. extra virgin coconut oils, cold pressed and sealed, from the brands COPRA® (national brand) and ISIS® (regional brand from Paraíba) in bacterial strains (E. coli and S. aureus), aiming to test the possible antimicrobial action against organisms bacterial parasites, with a sample of 2 bacterial strains (E. coli and S. aureus). At the end of the research, it was found that coconut oil from both brands did not perform bactericidal and / or bacteriostatic action on bacterial strains, even promoting the growth of colonies in the culture medium, presenting itself as an enriching potential for culture medium.